Ag-nanoparticles-loaded Ba0.85Ca0.15Ti0.9Zr0.1O3 for multicatalytic dye degradation. (15th January 2021) - Sharma, Moolchand; Singh, Gurpreet; Vaish, Rahul
Abstract: Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 (BCZTO) ferroelectric ceramic loaded with Ag nanoparticles (NPs) was explored for its photo/piezocatalytic performance. The presence of Ag loading on BCZTO ceramic was confirmed using electron microscopes. X-ray photoelectron spectroscopy revealed the metallic chemical state of Ag NPs loaded on the surface of BCZTO ceramic. The absorbance spectrum of the Ag-loaded BCZTO sample showed a visible light absorption hump due to the phenomenon of surface plasmonic resonance. During the photocatalysis process, the ˜ 99% of rhodamine B (RB) dye was degraded in aqueous solution using the Ag-loaded BCZTO sample, showing its promising photocatalysis activity. During the piezocatalysis process, the ˜ 95% of RB dye was degraded using the Ag-loaded BCZTO sample, showing its promising piezocatalytic activity. The ·OH radical species were found responsible for the photocatalytic and piezocatalytic performance. The photo/piezocatalytic performance was found to be consistent over five cycles, indicating promising reusability of the Ag-loaded BCZTO sample.